Revision of the family carabodidae (Acari, oribatida) v. fourth part. two new species of the genus congocepheus from the republic of Rwanda: Congocepheus rwandensis sp. n., and congocepheus kayoveae sp. n - Fernández, Néstor Alfredo (2016)
Two new species from Rwanda are described utilizing optical and scanning electron microscope observations: Congocepheus rwandensis sp. n. and Congocepheus kayoveae sp. n. are compared to Congocepheus taurus Balogh 1961.